Hair Growth and Antibacterial Effects of Nanoparticle-Based Cosmeceutical Tonic from Pogostemon cablin and Morus alba Leaves - Dyavaprathivi, Made Anindya Ayu; Maisa, Yustrida; Sandhiutami, Ni Made Dwi (Sciences of Pharmacy, 2025)
Hair loss affects a substantial portion of the global population, regardless of age or gender. One effective strategy to address this problem is the use of hair tonics that stimulate hair follicle activity and promote hair growth. This study developed an innovative cosmeceutical nanoparticle-based hair tonic combining Nilam and Mulberry leaf extracts, termed nanoNilamBerry. The formulation was prepared using the ionic gelation method and evaluated on rabbits over 28 days by assessing hair length, growth rate, and hair weight. The nanoNilamBerry formulation fulfilled the physicochemical requirements of a nanoparticle system and demonstrated good stability at 4 °C, 25 °C, and 40 °C for up to 28 days. In antibacterial assays against Staphylococcus epidermidis, the Nilam–Mulberry extract produced an inhibition zone of 16.36 ± 0.35 mm, while nanoNilamBerry exhibited a larger zone of 18.4 ± 0.30 mm. The hair tonic formulation showed no signs of skin irritation. The nanoNilamBerry treatment resulted in a hair growth rate of 0.13 ± 0.03 cm/day and a final hair weight of 32.36 mg, compared to 0.09 ± 0.01 cm/day and 27.3 ± 0.31 mg for the simple Nilam–Mulberry extract. Overall, the nanoNilamBerry hair tonic demonstrated superior efficacy, promoting hair growth 3.04 times faster than the untreated control and 1.45 times faster than the non-nano extract combination. These findings indicate that nanoNilamBerry not only provides effective antibacterial protection but also significantly enhances hair follicle stimulation and growth performance.